First record of the genus Neostatherotis Oku from China, with the descriptions of four new species (Lepidoptera: Tortricidae: Olethreutinae) - Luo, Jiuyang; Fei, Yao; Yu, Haili (Zootaxa, 2015)
The tortricid genus Neostatherotis Oku, 1974 is newly reported from China, and four species are described as new: N. psilata, sp. nov., N. sparsula, sp. nov., N. angustata, sp. nov., and N. breviuscula, sp. nov. Morphological descriptions and illustrations are provided, and a key for identification of the Chinese species is given.